Office workers' perceived barriers and facilitators to taking regular micro-breaks at work: a diary-probed interview study - Huang, Yitong; Benford, Steve; Hendrickx, Hilde; Treloar, Rob; Blake, Holly (Springer Verlag, 2017)
Research has suggested regular breaks in sedentary office work are im-portant for health, wellbeing and long-term productivity. Although many comput-erized break reminders exist, few are based on user needs and requirements as determined by formative research. This paper reports empirical findings from a diary-probed interview study with 20 office workers on their perceived barriers and facilitators to taking regular micro-breaks at work. This work makes two contributions to the Persuasive Technology (PT) community: a diagnosis of the full range of determinants and levers for changing office work break behaviours; a demonstration of applying the Behaviour Change Wheel (BCW), an intervention development framework originating from Health chology, to elicit theory-based design rec-ommendations for a potential PT.